Fulham 878–79: a new consideration of Viking manoeuvres - Baker, John; Brookes, Stuart (Brepols Publishers, 2012)
This paper uses evidence from a variety of disciplines in order to re-evaluate an apparently enigmatic event reported in several early sources – the landing of a Viking force at Fulham in 878. It examines the vocabulary of written accounts of their activities, sets archaeological evidence for a military camp at the site within a wider context, and gives further consideration to the strategic background of that location within a military landscape. These combined approaches, it is argued, allow a more detailed picture of this Viking war-band and its military significance to emerge.